2022
DOI: 10.1039/d2cc04721g
|View full text |Cite
|
Sign up to set email alerts
|

Anthraquinone-intercalated V2O5 with Al3+ for superior zinc-ion batteries: reversible transformation between disorder and order

Abstract: Oxygen-deficient anthraquinone (AQ)-intercalated vanadium oxide displays an ultralong lifespan in the electrolyte with Al3+ due to the dual-pillar of AQ/Al3+ and reversible disorder–order conversion on the (00l) facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…However, the peak gradually becomes weaker during the 1 st discharge process and finally disappears at the 1 st fully discharged state (discharge to 0.2 V) due to the intercalation of Zn 2+ into the (001) lamellar interstice. 33–36,52,54 In addition, the characteristic peak of H x V 2 O 5 at 33.4° is also observed during the 1 st discharge process, suggesting that a similar partial phase transition of DA-VO → Zn-doped H x V 2 O 5 happens at the DA-VO electrode. However, during the subsequent charge process, the diffraction peak of H x V 2 O 5 gradually becomes weaker and finally disappears at the 1 st charged state (charge to 1.6 V) accompanied by the vanishment of the characteristic peaks of DA-VO at 47.1° and 50.3°.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…However, the peak gradually becomes weaker during the 1 st discharge process and finally disappears at the 1 st fully discharged state (discharge to 0.2 V) due to the intercalation of Zn 2+ into the (001) lamellar interstice. 33–36,52,54 In addition, the characteristic peak of H x V 2 O 5 at 33.4° is also observed during the 1 st discharge process, suggesting that a similar partial phase transition of DA-VO → Zn-doped H x V 2 O 5 happens at the DA-VO electrode. However, during the subsequent charge process, the diffraction peak of H x V 2 O 5 gradually becomes weaker and finally disappears at the 1 st charged state (charge to 1.6 V) accompanied by the vanishment of the characteristic peaks of DA-VO at 47.1° and 50.3°.…”
Section: Resultsmentioning
confidence: 84%
“…However, during the subsequent discharge/charge process, this characteristic peak disappears, which is due to the (de)intercalation of Zn 2+ into the (001) interlayer space, thus decreasing the crystallinity of the lattice plane. [33][34][35][36]52,54 However, the diffraction peaks of DA-VO (S) at 47.1°and 50.3°are still maintained during the whole 1 st and 2 nd discharge/charge cycles, indicating the structural retention of DA-VO (S). Notably, upon the 1 st discharge cycle to 1.0 V, a new diffraction peak is observed at around 33.4°, which is ascribed as the strongest diffraction peak of H x V 2 O 5 (PDF # 40-1114), indicating the formation of Zn-doped H x V 2 O 5 with the co-intercalation of H + and Zn 2+ .…”
Section: Ex-situ Characterization Of the Da-vo (S) And Da-vo Electrodesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it can be observed that the (002) (d = 0.69 nm) lattice fringe is divided into smaller lattice fringes of (003) (d = 0.46 nm) and (006) (d = 0.23 nm) facets (Figure 3d). 43 Furthermore, large amounts of crystalline defects are observed in the nanosheet (Figure 3d), which probably can act as active sites for the storage of Na + to improve the capacity. 20,21 The prominent spots in the SAED pattern can be well indexed to (002), ( 200), ( 110), ( 005), ( 008), (009), and (0 0 12) planes (Figure S6), consistent with the XRD pattern of (p-TQ)-VO.…”
Section: Inorganicmentioning
confidence: 99%
“…The intercalants can also be organic molecules; however, mainly protonated organic amines have been investigated as organic molecules. [20][21][22][23][24] For example, Ma et al introduced ethylenediamine in V 7 O 16 , which provided a high specific capacity and surprising longterm cyclic stability in Zn 2+ storage. 20 Based on this, we considered that redox-active organic species such as 2-methylanthraquinone (denoted as 2-M-AQ) can also be employed as lamellar pillars between the V-O-V layers to expand the interlayer distance.…”
Section: Introductionmentioning
confidence: 99%